Landslide Potential Analysis using Geographic Information System and Analytical Hierarchy Process (AHP) (Case Study: Taktakan District, Serang City) - Mina, Enden; Fathonah, Woelandari; Kusumah, Rama Indera; Nurjanah, Ina Asha; Rafsanjaya, Aditiya (Jurnal Fondasi, 2025)
This research aims to analyze the landslide potential in Taktakan Sub-district, Serang City, which is prone to landslides due to geographical and hydrometeorological factors. The analysis was conducted using Geographic Information System (GIS) method with QGIS software and Weighted Linear Combination (WLC) approach combined with Analytical Hierarchy Process (AHP). Factors causing landslides, such as slope, rainfall, geology, and land use, were analyzed based on the weights obtained from respondents' questionnaires. The results showed that rainfall has the greatest influence (42%), followed by slope (37%), geology (11%), and land use (10%). The highest landslide potential is found in Taktakan sub-district, with the dominant vulnerability level in the medium class (50.73%), while the high and very high risk areas are 20.65% and 3.66%, respectively. This study concludes that high rainfall and steep slopes are the main factors that increase the risk of landslides in the area